The Effect of Sales Growth and Profitability on Financial Distress - Suci Ramadhani; Rindy Citra Dewi; Ronni Andri Wijaya (UPI YPTK Journal of Business and Economics, 2020)
This study aims to describe and estimate the effect of sales growth and profitabilitas on financial distress with leverage as the control variable in Manufacturing consumer goods industry sector and company in the chemical and basic industry sector listed on the Indonesian Stock Exchange in the period 2014-2018. Base on result of hypothesis testing it can be concluded that Sales Growth has no significant effect on Financial Distress. Profitabilitas has a significant effect on the Financial Distress. Sales Growth and Profitabilitas has a significant effect on the Financial Distress. Sales Growth has not significant effect on the Financial Distress with Leverage as the control Variable. Profitabilitas has a significant effect on the Financial Distress with Leverage as the control Variable. Sales Growth and Profitabilitas has a significant effect on the Financial Distress with Leverage as the control Variable. Leverage has a significant effect on the Financial Distress in manufacturing consumer goods industry sector and company in the chemical and basic industry sector. The company is expected to be able to improve financial performance, by paying attention to sales growth and profitabilitas so that investors are motivated to invest their shares in the desired company.